ANALISIS APLIKASI METODE GENETIC ALGORITHM (GA) UNTUK PENENTUAN LETAK SUMUR PRODUKSI VERTIKAL PADA LAPANGAN MINYAK DENGAN LAPISAN JAMAK YANG DIPRODUKSIKAN SECARA BERSAMAAN - Supriyadi
The method for determining the location of new production well in an oil field having multilayer reservoir is usually done with conventional method of using trial and error. The problem encountered in the application of this conventional method is time consuming because of the plentiful and heterogeneous data, especially in the large field. A method is proposed by implementing Genetic Algorithm for solving those problems. This final project aims to analyze that Genetic Algorithm (GA) application. This GA application is used for determining the location of new vertical well by evaluating fitness function which is proposed for searching the maximum production from a well. This application requires three main properties of reservoir rocks, i.e., porosity, permeability, and oil saturation as input data. An oil field with multilayer reservoir is used for analyzing GA application by comparing its result with the result from trial and error in maximizing the recovery factor. The developed GA application is able to give results which are almost same or even better compared to the conventional method in shorter time and with simpler kind of data